Let f(x) and g(x) defined as f(x) = x-5, g(x) = x²-1. Find:
a. f+g
b. f-g
c. f•g
d. f/g
e. g/f
Answers
Answered by
0
Step-by-step explanation:
(f+g)(x)=f(x)+g(x)
=x2+2x+1
(f−g)(x)=f(x)−g(x)
=x2−(2x+1)
=x2−2x−1
(fg)(x)=f(x).g(x)
=x2(2x+1)
=2x3+x2
(gf)(x)=g(x)f(x) (g(x)=0)
=2x+1x2 (x=−21)
Answered by
2
Answer:
a. f+g = x-5 + x^2 -1
= x^2 + x - 6
b. f-g = x-5 - ( x^2 -1 )
= x-5 - x^2 + 1
= - x^2 + x -4
c. fog = f [g (x) ]
= f [ x^2 -1 ]
= x^2 -1 -5
= x^2 -6
d. f/g = x-5 /x^2 -1
e. g/f = x^2 -1 / x -5.
Similar questions